Hypothetital Learning Trajectory: Bagaimana Mendesainnya Untuk Pembelajaran Matematika Di Sekolah Menengah Pertama? (Mathematical Proceedings of The Widya Mandira Catholic University, 2024)
In today's modern era, mathematics learning requires teachers to be able to develop learning models that pay attention to the characteristics of students, so it is important for teachers to know how to design hypothetical learning trajectory. This article aims to find out how to design a hypothetical learning trajectory for mathematics learning in junior high school. The method used in this writing is a literature study (library research). Hypothetical Learning Trajectory is a learning design about alleged student learning activities. In general, the hypothetical learning trajectory consists of three components, namely learning objectives, learning activities in order to achieve learning objectives, and hypotheses of the learning process related to the thinking process and understanding of students. In mathematics learning, hypothetical learning trajectories are designed by taking into account the obstacles experienced by students during the furniture process.